The Effect of Education on Portal Personal Health Record Use. - Casey, Imke (Online Journal of Nursing Informatics)
The purpose of this study was to examine the rate of portal personal health record (PHR) use among chronically ill older adults to evaluate the effectiveness of an educational intervention in improving PHR adoption, and to identify patients' thoughts about the PHR. The quasi-experimental study was performed at a primary care group practice in central Florida. Participants were recruited during provider appointments. Fifty participants completed the Background and Computer Questionnaire (DBQ) and received the educational intervention followed by a four-week follow-up phone survey. To evaluate the effectiveness of the educational intervention, the study pair matched participants, to form a non-participant control group. Participants' computer use comfort level increased significantly four weeks after the PHR educational intervention (Z = -1.668, p < 0.005). In addition, the amount of PHR use by the participant group (M = 1.08) was significantly higher, compared to the pair-matched control group (M = 0.16), U = 735.5, p = 0.001. Analysis of the qualitative component indicated that patients are willing to use the PHR if their laboratory results are up-to-date and available for review. Hands-on computer instructions are an effective method to increase PHR use among chronically ill adult primary care practice patients. Computer training and education promote and improve people's overall computer use comfort levels. Patients feel that the PHR is a valuable tool if their data are current and accessible.